Optical and electrical modulation in ultraviolet photodetectors based on organic one‐dimensional photochromic arrays. (23rd August 2021) - Geng, Yue; Zhao, Yingjie; Zhao, Jinjin; Zhai, Yu; Yuan, Meng; Wang, Xue‐Dong; Gao, Hanfei; Feng, Jiangang; Wu, Yuchen; Jiang, Lei
Abstract: Organic photochromic materials have drawn considerable attention for their potential applications in large‐scale and low‐cost optoelectronics owing to unique tunable physicochemical properties. For organic photodetectors, photochromic materials have realized optical and electrical engineering of semiconductor layers, which incorporate not only tunable performance, but also functionalities to optoelectronic devices. However, the essential challenge is to assemble large‐area photochromic micro‐ and nanostructure arrays with controllable geometry and precise alignment, which restricts the integration of multifunctional optoelectronic devices. Herein, we fabricate organic photochromic one‐dimensional (1D) arrays via a feasible solution process through the confined crystallization of organic molecules. By modulating and controlling the photoisomerization behaviors, these 1D photochromic arrays possess broad spectral tunability, which ensure tunable photoresponse. Furthermore, we investigate the crystallographic transition and electronic performance variation of these 1D photochromic arrays. By adjusting the dwell time of ultraviolet (UV) irradiation, the UV photochromic photodetectors realize tunable and repeatable responsivity from 85.6 to 0.709 mA/W. Our work provides new possibilities for optical and electrical engineering of photochromic microwires towards the integration of multifunctional optoelectronic devices. Abstract : Optical and electrical engineering of organic one‐dimensional (1D) photochromic arrays with strict alignment, precise position, and controllable geometry are achieved through an asymmetric‐wettability assembly system. Ultraviolet (UV) photodetectors based on photochromic microwires exhibit tunable optoelectronic performance by efficiently modulating the current transport.